Factors Associated with the Prevalence of External Compression Headache Attributed to Personal Protection Equipment Usage - Restu Susanti; Yuliarni Syafrita (Universitas Islam Bandung, 2022)
Personal protective equipment (PPE) in the COVID-19 pandemic era is essential for healthcare workers to decrease the risk of infection. The PPE, such as N95 masks and goggles, can trigger external-compression headache (ECH). This study aimed to determine the factors associated with the prevalence of ECH attributed to PPE usage. It was an analytic-observational study with a cross-sectional design conducted at Dr. M. Djamil Hospital Padang in May 2020. The subjects were healthcare workers (doctors and nurses) who used level 3 PPE for a minimum of 4 hours. The diagnosis of ECH was determined by the International Classification of Headache Disorders (ICHD) 3rd edition criteria. The Headache Screening Questionnaire (HSQ) determined the pre-existing primary headaches. The association between variables was analyzed using chi-square and Kruskal-Wallis tests. P-value<0.05 was considered statistically significant. A total of 113 healthcare workers participated in this study, consisting of 46 (40.7%) males and 67 (59.3%) females. The median age was 30 (23–46) years. ECH occurred in 102 (90.3%) respondents. Pre-existing primary headaches were present in 79 (69.9%) respondents, including migraine in 28 (23.6%) and tension-type headaches (TTH) in 46 (40.7%) respondents. The frontalis (69%) and temporalis (50.4%) were the most affected muscles. In this study, the significant factor associated with ECH was pre-existing primary headache (p=0.001, OR=7.795). There was a significant association between the pre-existing TTH (p=0.022) and ECH. There was a non-significant association between pre-existing migraine and ECH (p=0.284). In conclusion, the pre-existing primary headache was associated with the prevalence of ECH attributed to PPE usage.